Ecological approach for assessing drill quality. A case study - Daicu, Raluca; Ditu, Valentin; Oancea, Gheorghe (IOP Conference Series: Materials Science and Engineering, 2018)
The quality of drills is classically appreciated by measuring the effective cutting time until the appearance of the admissible wear on the land surface. The experimental tries lead to material consumption and also to resulted chips which, in most cases, are cast as a pollution element. The proposed method for assessing quality is based on measuring the electrical current at cutting and substantially reduces the quantity of resulted chips. The case study was developed for HSS ϕ8 drills and shows the advantages of the method and its ecological impact. The experiments were performed using 1C45 steel workpiece material.